Implementation of Law Enforcement Towards the Regulation of Street Clowns in Gorontalo City - Rohana Mahmud; Sukarman Kamuli; Nopiana Mozin (Fox Justi : Jurnal Ilmu Hukum, 2026)
The phenomenon of street clowns in urban areas, particularly in Gorontalo City, is a form of social problem that arises due to economic pressures and limited employment opportunities, and has implications for disrupting public order. Although it has been regulated in Regional Regulation No. 1 of 2018 concerning Public Order, the practice of street clowns continues to occur in public spaces. This study aims to analyze the implementation of Regional Regulation No. 1 of 2018 on controlling street clowns and identify factors that influence the effectiveness of law enforcement. This study uses an empirical legal research type with a descriptive qualitative approach. The research location was carried out in Gorontalo City, specifically at road intersections and public spaces. The research informants numbered 6–8 people consisting of officers from the Civil Service Police Unit, the Social Service, street clowns, and road users, who were selected purposively because they were considered to understand the problem being studied. The data used includes primary and secondary data, obtained through interviews, observation, documentation, and literature review. These data were then analyzed through data reduction, data presentation, and conclusion drawing, with validity testing through source triangulation. The results of the study indicate that policy implementation has been running quite well from an institutional perspective through socialization, enforcement, and guidance. However, it has not been fully effective due to ongoing communication constraints, limited resources, unequal distribution of guidance, and inconsistent law enforcement. Furthermore, economic factors are the primary cause of the continued existence of the street clown phenomenon. Therefore, an approach that is not solely repressive but also encompasses a sustainable social empowerment program is needed. These findings provide important implications for public policy development, particularly in creating more comprehensive and long-term solution-oriented handling.